Pengaruh Suplementasi Seng Sulfat 40 mg/hr Selama 12 Minggu terhadap Kadar Sitokin proinflamasi TNF-α, IL-1β dan IL-6 Pada Penderita Kusta Multi Basiler - Joko Kurnianto; Hertanto WS; Prasetyowati Prasetyowati; Suharyo HS (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
The role of zinc as an anti-oxidant and anti-inflammatory has been widely proven, this substance is relatively inexpensive and easily available to the public. Serum zinc levels of leprosy patients and patients with leprosy reactions are lower compared to healthy people, and proinflammatory cytokines including TNF-α, IL-1β and IL-6 play a role in the mechanism of leprosy reactions. Research on the effect of zinc supplementation on leprosy sufferers who have not experienced a reaction has not been done. Objective: To analyze the effect of 40 mg / day dose of zinc sulphate supplementation for 12 weeks on the levels of proinflammatory cytokines and the incidence of reactions in type MB leprosy patients. An experimental study with a randomized control group pre and post test design approach, the subjects of this study were MB patients with 121 patients who did not experience a leprosy reaction, the sample was taken randomly as many as 31 patients as a supplementation group (treatment), and 31 patients as Control group. BMI measurements, food intake by re-call method, Hb level using Hematology Analyzer, serum zinc levels using Atomic Absorption Spectrophotometry (AAS) method, TNF-α, IFN-γ, and IL-1β levels used the ELISA method. Data analysis using chi-square correlation statistical test and mean (mean) test. Zinc sulfate supplementation dose of 40 mg / day for 12 weeks in type MB leprosy patients was able to maintain a decrease in zinc levels of 1.22 pg / dL higher than leprosy patients who did not receive zinc supplementation, reduce levels of IL-1β (p: 0.032 ) However, statistically there is insufficient evidence to reduce levels of TNF-α (p: 0.063) and IL-6 (p: 0.389) and risk factors. Food intake is associated with the incidence of leprosy reactions (p 0.05).Keywords:Supplementation, cytokines, leprosy type MB.Conclusion: The most recent findings in this study were 40 mg / day supplementation of zinc sulfate for 12 weeks in MB type leprosy patients able to maintain a decrease in serum zinc levels, reduce IL-1β levels, and risk factors. Food intake correlated with the incidence of leprosy reactions